OsDIRP1, a Putative RING E3 Ligase, Plays an Opposite Role in Drought and Cold Stress Responses as a Negative and Positive Factor, Respectively, in Rice (Oryza sativa L.) - Cui, Li Hua; Min, Hye Jo; Byun, Mi Young; Oh, Hyeong Geun; Kim, Woo Taek (Frontiers in Plant Science, 2018)
As higher plants are sessile organisms, they are unable to move to more favorable places; thus, they have developed the ability to survive under potentially detrimental conditions. Ubiquitination is a crucial post-translational protein modification and participates in abiotic stress responses in higher plants. In this study, we identified and characterized OsDIRP1 (Oryza sativa Drought-Induced RING Protein 1), a nuclear-localized putative RING E3 ubiquitin (Ub) ligase in rice (Oryza sativa L.). OsDIRP1 expression was induced by drought, high salinity, and abscisic acid (ABA) treatment, but not by low temperature (4°C) stress, suggesting that OsDIRP1 is differentially regulated by different abiotic stresses. To investigate its possible role in abiotic stress responses, OsDIRP1-overexpressing transgenic rice plants (Ubi:OsDIRP1-sGFP) were generated, and their phenotypes were analyzed. The T4 Ubi:OsDIRP1-sGFP lines showed decreased tolerance to drought and salt stress as compared to wild-type rice plants. Moreover, Ubi:OsDIRP1-sGFP progeny were less sensitive to ABA than the wild-type during both germination and post-germination growth. In contrast, Ubi:OsDIRP1-sGFP plants exhibited markedly higher tolerance to prolonged cold (4°C) treatment. These results suggest that OsDIRP1 acts as a negative regulator during drought and salt stress, whereas it functions as a positive factor during the cold stress response in rice.